METHODOLOGY OF ENGLISH LANGUAGE TEACHING IN PRESCHOOL CHILDREN. - BALLIYEVA SADOQAT ABULQOSIM QIZI; JO‘RAYEV BAHODIR ALISHER O‘G‘LI; KAYUMOVA MOHINUR MURODULLAEVNA (TADQIQOTLAR.UZ, 2024)
Abstract: in the article "Pre-school education" The process of teaching English to children, effective support, and the need to implement it today are highlighted.